1999
DOI: 10.1016/s0304-3940(99)00180-9
|View full text |Cite
|
Sign up to set email alerts
|

Met-enkephalin-induced mobilization of intracellular Ca2+ in rat intracardiac ganglion neurones

Abstract: The effects of Met-enkephalin on Ca 2+-dependent K + channel activity were investigated using the cell-attached patch recording technique on isolated parasympathetic neurones of rat intracardiac ganglia. Large-conductance, Ca 2+ -dependent K + channels (BK Ca ) were examined as an assay of agonist-induced changes in the intracellular free calcium ion concentration ([Ca 2+ ] i ). These BK Ca channels had a conductance of ˜200 pS and were charybdotoxin-and voltage-sensitive. Caffeine (5 mM), used as a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Thapsigargin also eliminated the rise in [Ca 2ϩ ] i elicited by bath application of 5 mM caffeine (Fig. 3D), which has been shown to evoke release of Ca 2ϩ from intracellular stores in these cells (49 3 ) and a second that is sensitive to ryanodine and caffeine (39,49). The PACAP/VIP receptors have been shown to mobilize Ca 2ϩ from both IP 3 -and ryanodine/caffeine-sensitive stores in other cell types (44,46).…”
Section: Pacap and Vip Directly Increase Freementioning
confidence: 76%
See 1 more Smart Citation
“…Thapsigargin also eliminated the rise in [Ca 2ϩ ] i elicited by bath application of 5 mM caffeine (Fig. 3D), which has been shown to evoke release of Ca 2ϩ from intracellular stores in these cells (49 3 ) and a second that is sensitive to ryanodine and caffeine (39,49). The PACAP/VIP receptors have been shown to mobilize Ca 2ϩ from both IP 3 -and ryanodine/caffeine-sensitive stores in other cell types (44,46).…”
Section: Pacap and Vip Directly Increase Freementioning
confidence: 76%
“…Microfluorometric Measurements-The calcium-sensitive dye fura-2/AM was used for measuring intracellular free calcium concentrations in intracardiac neurons, as previously described (39). Cells plated on coverslips were incubated for 1 h at room temperature in physiological saline solution (PSS) consisting of 140 mM NaCl, 3 mM KCl, 2.5 mM CaCl 2 , 1.2 mM MgCl 2 , 7.7 mM glucose, and 10 mM HEPES (pH to 7.2 with NaOH), which also contained 1 M fura-2/AM and 0.1% Me 2 SO.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, ryanodine, in micromolar concentrations is an inhibitor of caffeine-induced Ca 2ϩ release from intracellular Ca 2ϩ stores in rat autonomic neurons (Smith and Adams 1999;Thayer et al 1988). Focal application of caffeine (10 mM) evoked a transient [Ca 2ϩ ] i increase (114 Ϯ 19 nM, n ϭ 4) that was inhibited by bath application of 10 M ryanodine (14 Ϯ 5% of control, n ϭ 4, P Ͻ 0.005) as shown in Fig.…”
Section: Nachr Activation Induces Ca 2ϩ Release From Internal Ca 2ϩ Smentioning
confidence: 99%
“…Furthermore, Met-enkephalin-induced increase of intracellular Ca 2? in rat intracardiac neurons was found to be inhibited by ryanodine (Smith and Adams 1999). All these findings indicated that Ca 2?…”
Section: The Central Role Of Ca 2?mentioning
confidence: 76%
“…or cyclic ADP ribose (Zalk et al 2007). Although all three isoforms of the RyRs (RyR1-3) have been found in the central nervous system, RyR2 is the most prevalent (Smith and Adams 1999). DOR activation has been reported to increase the release of Ca 2?…”
Section: The Central Role Of Ca 2?mentioning
confidence: 99%